SOSIALISASI UPAYA PENCEGAHAN INFEKSI JAMUR PADA PENDERITA DIABETIK DI KELURAHAN AIR PUTIH - Kamil, Kamil; Raudah, Siti (Jurnal Pengabdian Masyarakat Teknologi Laboratorium Medik Borneo, 2022)
Diabetes mellitus (DM) is a public health problem and is one of four non-communicable diseases that receive priority follow-up targets for world leaders. The incidence of DM increases with age. Chronic hyperglycemia in DM is associated with long-term damage, and dysfunction of several organs, including the eyes, kidneys, nerves, heart and blood vessels. In addition to these organs, the skin is one of the organs that is often affected by DM. Skin manifestations in the form of infection are one of the chronic complications that are often seen in DM patients. High blood glucose levels cause skin glucose levels in DM patients to increase and facilitate the emergence of skin manifestations in the form of dermatitis, bacterial infections, fungal infections, and others. Infections in people with diabetes differ from one place to another, depending on the type of infection acquired, the level of environmental sanitation, nutritional status, and the level of individual immunity. Chronic infection can cause pain loss, due to nerve damage neuropathy and/or foot ischemic. This community service aims to provide health education and see the existence of fungal infections in the form of hyphae and spores on the skin scrapings of DM patients in Air Putih Village.